SME’s perspective on psychosocial risks: From identifying to intervening in four countries - Costa, P.; Ramos, S.; Silva, S.; Passos, A.; Tavares, S.; Bretones, F.; Delgado, A.; Doulougeri, K.; Georganta, K.; Giacominelli, B.; Gonzalez, J.; Gonzalez, R.; et al. (12th EAOHP Conference. Occupational health psychology in times of change: Society and the workplace, 2016)
Introduction: Certain aspects of the work design or the organization as well as the social context of work may lead to negative physical, psychological and social outcomes. These aspects are considered psychosocial risks. Portugal, Spain, Italy, and Greece are facing the biggest consequences of the economic crisis with psychosocial risks being exacerbated. In these countries, small and medium enterprises play an important role in the economy. This paper presents the quantitative data from the project, collected in those four countries. The main goal of the survey was to determine the SMEs’ perspective about emergent psychosocial risks, difficulties and concerns related to its prevention as well as to assess their knowledge and existing practices regarding psychosocial risks prevention.